Yield performance of some maize varieties as influenced by irrigation management at different growth stages - Kobir, Md Shahriar; Rahman, Md Rashedur; Islam, AKM Mominul; Paul, Suchana; Islam, Md Monirul; Farid, Md Nasirul; Hajong, Pradip (Research in Agriculture Livestock and Fisheries, 2019)
The experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh, during the period from December 2017 to April 2018 to study the yield performance of some maize varieties as influenced by irrigation management at different growth stages. The experiment was laid out in a split plot design with three replications where factor (A) irrigation stages were allocated in main plots and factor (B) varieties were distributed in sub plots. In factor A five irrigation management viz. I0 = (No irrigation), I1= (Four leaf stage + eight leaf stage + tasselling stage+ grain filling stage), I2= (Four leaf stage+ eight leaf stage + tasselling stage), I3= (Eight leaf stage + tasselling stage +grain filling stage), I4=(Four leaf stage + tasselling stage+ grain filling stage), I5=(Four leaf stage+ eight leaf stage+ grain filling stage) and in factor B three varieties viz. V1= (BARI hybrid vutta-9), V2= (BARI hybrid vutta-13), V3= (pacific-559) were included as treatments in the experiment. Data were collected on yield and yield contributing characters. The highest grain yield (5.88 t/ha) was obtained with the water management treatment I1(Four leaf stage + eight leaf stage + tasselling stage+ grain filling stage) which is statistically similar to treatment I4(Four leaf stage + tasselling stage+ grain filling stage) and highest grain yield (5.87 t/ha) obtained due to the varietal factor V3 (pacific-559). Interaction between I1 irrigation treatment and V3 varietal factor (I1V3) were found to be the best combination which is statistically similar to I4V3 interaction. As I4 treatment and I4V3 interaction are cost effective than I1 treatment and I1V3 interaction, respectively, irrigation should be given at four leaf stage, tasselling stage, and grain filling stage with variety pacific-559 for better performance in maize production. Res. Agric., Livest. Fish.6(1): 57-67, April 2019